Epigenetic inheritance of spine formation in sago palm (Metroxylon sagu Roettb). - Novero, Annabelle U.; Mabras, Ma. Brigida; Esteban, Hannah Jean.
The formation of spine is a primitive evolutionary event in plants. In sago palm, studies reporting the results of RAPD and AFLP analyses showed lack of significant genetic variation among spiny and non-spiny plants. This observation led us to the hypothesis that spine formation may be an epigenetic event. The inheritance of spine formation is of high interest to plant breeders because spineless plants are preferred due to their more cost efficient handling. In this study, we analyzed the DNA methylation patterns of sago palm DNA by distinguishing methylated (5dmC) and non-methylated cytosine (dC) in HPLC analysis. We optimized HPLC conditions (nucleoside digestion, retention time of mobile phase and stop time) and identified the factors (growth environment and age of the palms) which may have affected DNA methylation levels. Our data show that a flow rate of 0.2 mL/min using C18 columns was most suitable in distinguishing between dC and 5mdC peaks. There was significant difference in methylation percentage between spiny (21.5%) and non-spiny (11.5%) palms at P = 0.05, indicating that the formation of spine was an epigenetic event. Further, there was an indication that the wet environment may have caused the epigenetic event and that spine formation was also age dependent. The influence of these factors will be confirmed using a more sensitive technique such as the methylation-sensitive amplified polymorphism (MSAP) analysis.
Keywords: Sago